ETHNIC MOTIFS IN THE AUTHOR’S WORKS OF LYUDMILA SEMIKINA OF THE 1960s-1990s IN THE CONTEXT OF THE SYNTHESIS OF ARTS - Papeta, Olena (Theory and practice of design, 2024)
Purpose. Identify ethnic motifs in L. Semikina’s author’s clothing designs; to carry out a stylistic analysis of figurative and plastic solutions of costumes from the 1960–1990 collections in order to determine their cultural-historical and semantic connections; consider the peculiarities of the creative method of L. Semikina in the context of innovative trends and compositional and color innovations, show the synthesis of archaic artistic and stylistic solutions with modern approaches in clothing design. Methodology. The method of archival and bibliographic research, the historical method, and the method of theoretical generalizations are applied. The method of synthesis is to reveal the relationships between the artist and society. The method of art history and, in particular, figurative and stylistic analysis was applied in the process of identifying ethnic motifs in the works of L. Semikina. Results. The author’s series of costumes by L. Semikina from the collections of 1960–1990 is a vivid and convincing evidence of how a modern artist-designer, turning to the inexhaustible source of ideas, images and forms of the cultural heritage of Ukraine, finds new forms of spiritual and aesthetic continuity. Her original outfits are an innovative form of designer’s approach to the problem of rethinking the ethnic features of the costume, from historical stylizations to mythopoetic reconstructions. In the context of the problem of the analysis of the ethnic morphology of clothing, L. Semikina’s work is an attempt to spiritually reproduce the constructive and sacral function of the costume, with a consistent reflection of the design idea in the material. Scientific novelty. The unknown facts of the creation of L. Semikina’s author’s collections and unpublished ethnic costumes from the artist’s private collection have been introduced into scientific circulation; the artistic analysis of the figurative and plastic solution of costumes from the 1960–1990 collections were carried out; the specificity of the artistic interpretation of historical and national motifs in author’s clothing models was revealed. Practical relevance. The results of the research will be useful to scientists and scientific and pedagogical workers in the process of researching the cultural and artistic movement of nonconformism in Ukraine, studying the ethnostylistics of Ukrainian author’s costumes, and teaching specialized disciplines in fashion design. For designers, the conducted research has a purely practical value in creating modern clothes using ethnic motifs.